Procreative well-being and pornography – analyzing the script. Public health implications revealed through an ethological lens. Issue 6 (18th August 2019) - Butler, Mark H.
Abstract: An ethological model of human procreative well-being is proposed and the goodness-of-fit of pornography's script to that model is considered. Deducing an evolutionary template for procreative well-being from an ethological analysis links attachment dynamics to procreative success. Alongside parent–child attachment, pair-bond attachment in the procreative couple looms large as an element of optimal procreative relationship structure and quality. Key elements of pair-bond attachment are documented. Turning next to an empirical examination of the sexual behavioral system in humans, we see evidence of an evolutionary design supportive of attachment as well as reproductive exigencies of procreative well-being. Sexual system mechanisms promoting both reproduction and attachment are evident in the evolutionary design. We next employ script theory to identify key elements of the sexual script promulgated by pornography. Joining these two analyses, we compare the evolutionary, attachment-based template for procreative success in juxtaposition to pornography's sexual script to evaluate the goodness-of-fit of pornography use to attachment success and, by extension, procreative well-being. We conclude that there is an ethological case to be made for considering pornography use as a public health risk. Implications of the model of procreative well-being for the practice of couple therapy are given mention.